Dexamethasone and Risk of Bleeding in Children Undergoing Tonsillectomy. (3rd February 2014) - Mahant, Sanjay; Keren, Ron; Localio, Russell; Luan, Xianqun; Song, Lihai; Shah, Samir S.; Tieder, Joel S.; Wilson, Karen M.; Elden, Lisa; Srivastava, Rajendu; ,
Abstract : Objective: To determine whether dexamethasone use in children undergoing tonsillectomy is associated with increased risk of postoperative bleeding. Study Design: Retrospective cohort study using a multihospital administrative database. Setting: Thirty‐six US children's hospitals. Subjects: Children undergoing same‐day tonsillectomy between the years 2004 and 2010. Methods: We used discrete time failure models to estimate the daily hazards of revisits for bleeding (emergency department or hospital admission) up to 30 days after surgery as a function of dexamethasone use. Revisits were standardized for patient characteristics, antibiotic use, year of surgery, and hospital. Results: Of 139, 715 children who underwent same‐day tonsillectomy, 97, 242 (69.6%) received dexamethasone and 4182 (3.0%) had a 30‐day revisit for bleeding. The 30‐day cumulative standardized risk of revisits for bleeding was greater with dexamethasone use (3.11% vs 2.71%; standardized difference 0.40% [95% confidence interval, 0.13%‐0.67%]; P =. 003), and the increased risk was observed across all age strata. Dexamethasone use was associated with a higher standardized rate of revisits for bleeding in the postdischarge time periods of days 1 through 5 but not during the peak period for secondary bleeding, days 6 and 7. Conclusions: In a real‐world practice setting, dexamethasone use was associated with a small absolute increased risk of revisits for bleeding. However, the upper bound of this risk increase does not cross published thresholds for a minimal clinically important difference. Given the benefits of dexamethasone in reducing postoperative nausea and vomiting and the larger body of evidence from trials, these results support guideline recommendations for the routine use of dexamethasone.